Construct Validity, Criterion Validity, and Internal Consistency of GOT-Cog©, a Novel Occupational Therapy Cognitive Screen. - Meise, Emily; Corbett, John; Meyer, Amanda; Grevelding, Pete; Hrdlicka, Henry C. (American Journal of Occupational Therapy)
Importance: No single cognitive screen adequately captures the cognitive domains needed for inpatient occupational therapy treatment planning. Objective: To assess the construct validity of the Gaylord Occupational Therapy Cognitive (GOT-Cog©) screen, a novel comprehensive cognitive screen that evaluates functional cognition. Design: Randomized crossover controlled study design using the St. Louis University Mental Status (SLUMS) exam as a comparator. Setting: Long-term acute-care hospital. Participants: Participants were inpatients admitted to Gaylord Hospital who were ages 18 yr or older, prescribed occupational therapy services, with no documented history of dementia, Alzheimer's, or preexisting intellectual disability and no present aphasia. Intervention: During participants' initial occupational therapy evaluation, either the SLUMS or GOT-Cog were randomly delivered; the screen that was not delivered on admission was delivered 22 to 26 hr later by the same or a different clinician. Outcomes and Measures: GOT-Cog and SLUMS total scores and individual item and domain scores. Results: Ninety-eight participants yielded sufficient data for analysis. Total GOT-Cog and SLUMS scores positively correlated (p <.0001). All shared domains between GOT-Cog and SLUMS were significantly correlated (p ≤.0155); similarly, all unique domains showed significant correlations with both GOT-Cog and SLUMS total scores (p ≤.0194). No ordering effects were observed (p ≥.8081). Despite having 11 more items, GOT-Cog took only 6 min longer to complete (10 vs. 16 min; p <.0001). Both demonstrated adequate internal consistency. Conclusions and Relevance: The GOT-Cog has overall strong construct and criterion validity. Going forward, we will evaluate the rater reliability and responsiveness of the GOT-Cog. Plain-Language Summary: Occupational therapists evaluate clients' cognitive strengths and limitations in relation to activities of daily living and instrumental activities of daily living. Occupational therapists use this evaluation to help clients identify strategies to adapt to their specific environments, support their independence, and improve their ability to perform tasks. No cognitive screen currently exists that adequately evaluates a person's cognitive domains as part of treatment planning for inpatient occupational therapy. This study reviewed the construct validity, criterion validity, and internal consistency of the Gaylord Occupational Therapy Cognitive screen (GOT-Cog), a new comprehensive cognitive screen. The GOT-Cog was used with inpatients at a long-term acute-care hospital as part of their initial occupational therapy evaluation. The study found that the GOT-Cog has overall strong construct and criterion validity. Future studies will evaluate the interrater and intrarater reliability and responsiveness of this new cognitive screen. This study reviewed the construct validity, criterion validity, and internal consistency of the Gaylord Occupational Therapy Cognitive screen (GOT-Cog), a new comprehensive cognitive screen.